Refractive index and fourier transform infrared spectra of virgin coconut oil and virgin olive oil - Mat Yunus, Wan Mahmood; Yap, Wing Fen; Lim, Mei Yee (Science Publications, 2009)
This study presents the refractive index and FTIR spectra of virgin coconut oil and virgin olive oil that have been measured in the wavelength range from 491.0-667.8 nm. The measurement of refractive index was carried out using a minimum deviation method while the IR transmission ranging from 600-4000 cm-1 was measured using FTIR spectrometer respectively. The measurements were done at room temperature and the dispersion equations for the studied samples were verified and the Cauchy constants were obtained by fitting the experimental data to the Cauchy formula. For both, refractive index and Cauchy constants, the value obtained are higher in virgin olive oil as compared to virgin coconut oil. A similar result for FTIR absorption spectrum was also observed where the five important peaks explaining the stretching absorption due to aldehyde (C = O) and esters (C-O), bending absorption (methylene (CH2) and methyl (CH3) groups and double bond absorptions (C = O) were strong in virgin olive oil.